GABA Potency at GABAA Receptors Found in Synaptic and Extrasynaptic Zones - Mortensen, Martin; Patel, Bijal; Smart, Trevor G. (Frontiers in Cellular Neuroscience, 2012)
The potency of GABA is vitally important for its primary role in activating GABAA receptors and acting as an inhibitory neurotransmitter. Although numerous laboratories have presented information, directly or indirectly, on GABA potency, it is often difficult to compare across such studies given the inevitable variations in the methods used, the cell types studied, whether native or recombinant receptors are examined, and their relevance to native synaptic and extrasynaptic GABAA receptors. In this review, we list the most relevant isoforms of synaptic and extrasynaptic GABAA receptors that are thought to assemble in surface membranes of neurons in the central nervous system. Using consistent methodology in one cell type, the potencies of the endogenous neurotransmitter GABA are compared across a spectrum of GABAA receptors. The highest potency for GABA is measured when activating extrasynaptic-type α6 subunit-containing receptors, whereas synaptic-type α2β3γ2 and α3β3γ2 receptors exhibited the lowest potency, and other GABAA receptor subtypes that are found both in synaptic and extrasynaptic compartments, showed intermediate sensitivities to GABA. The relatively simple potency relationship between GABA and its target receptors is important as it serves as one of the major determinants of GABAA receptor activation, with consequences for the development of inhibition, either by tonic or phasic mechanisms.